King David as a Righteous Man in the Light of Qumran Literature and Post-Biblical Texts of Early Judaism - Biegas, Marcin (The Biblical Annals, 2026)
The present paper analyses the picture of David as a righteous man depicted in non-biblical Qumran texts and the literature of Early Judaism. The choice of such a broad research field results from the fact that no articles have been published so far that would examine this theme in detail based on the above compositions. Thus, undertaking this task is a justified endeavour. The paper will be divided into three parts. The first part will present the biblical background, mainly based on post-exilic literature. In the second part, fragments of four Qumran manuscripts – 4QMMT, CD, 1Q33 and 11Q5 – will be analysed. Finally, the literature of early Jewish writings containing depictions of David will be discussed. A thorough analysis of all these texts will show that David was a righteous man.